Positive evaluations may be shortlived: On outcomes and processes of a World Bank biodiversity project in a post-communist country - Maria Falaleeva; Felix Rauschmayer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2009)
International aid projects in post-communist countries were meant to support the existing systems of environmental protection during the transition period and also to introduce new standards of environmental governance. This paper looks at the role project evaluations can play in fulfilling these goals. While the outcomes of the World Bank project in the Belavezhskaya Pushcha national park in Belarus were evaluated positively after its (delayed) completion, an evaluation using the same criteria 10 years later challenges the long-term effectiveness of the project. Evaluating the implementation process, we see three interlinked reasons for this failure which can be generalized with regard to environmental governance in many post-communist countries even now: the predominance of the natural sciences, an unbalanced representation of the actors, and little knowledge regarding participatory methods. In order to introduce new standards for environmental governance, international aid projects should use ongoing project and, in particular, process evaluation as a tool to support communication between the donor organizations and the implementing agencies on the one hand and between the different actors in the receiving countries on the other.
Keywords: 360